THE MADRASAH’S HEADMASTER STRATEGIES IN STIMULATING STUDENTS’ INTEREST IN SCHOOLING - Nihali, Imran; Nimim, Nimim (JURNAL PENDIDIKAN GLASSER, 2023)
The research results show that the headmaster's strategy in stimulating students' interest in attending school involves direct visits to other schools to socialize and effectively utilize the educational environment (family and community) by collaborating with them to attract prospective students to continue their education at MTs Negeri 1 Bone Bolango. The obstacles faced by the headmaster in stimulating students' interest in attending school include: first, the lack of facilities or support systems for nurturing students' inteThe Madrasah’s headmaster should have strategy in advancing their madrasah. Without a strategy, the program of madrasah will not run. The development and progress of madrasah can be seen from the professional performance of the Madrasah’s headmaster and the headmaster be able to utilize the existing resources effectively and efficiently. This research aims to determine: 1) the strategies of the headmaster in stimulating students' interest in attending school at MTs Negeri 1 Bone Bolango, and 2) the obstacles and efforts made in stimulating students' interest in attending school at MTs Negeri 1 Bone Bolango. This is a qualitative research with a descriptive method. Data collection methods in this research include observation, interviews, and documentation. The research results show that the headmaster's strategy in stimulating students' interest in attending school involves direct visits to other schools to socialize and effectively utilize the educational environment (family and community) by collaborating with them to attract prospective students to continue their education at MTs Negeri 1 Bone Bolango. The obstacles faced by the headmaster in stimulating students' interest in attending school include: first, the lack of facilities or support systems for nurturing students' interests and talents, especially in the implementation of the independent learning curriculum, and other facilities. Second, the inability of the community to financially support their children's education at MTs Negeri 1 Bone Bolango due to the distance between their homes and the location of the madrasah. Efforts undertaken to address these challenges include: 1) proposing scholarships to the government for financially disadvantaged students and providing dormitory facilities for students who live far from the madrasah, and 2) providing facilities that support the teaching and learning process in the classroom, such as LCDs and other educational media. In addition, efforts are made to add classrooms, sports facilities, laboratories, and other amenities.rests and talents, especially in the implementation of the independent learning curriculum, and other facilities. Second, the inability of the community to financially support their children's education at MTs Negeri 1 Bone Bolango due to the distance between their homes and the location of the madrasah. Efforts undertaken to address these challenges include: 1) proposing scholarships to the government for financially disadvantaged students and providing dormitory facilities for students who live far from the madrasah, and 2) providing facilities that support the teaching and learning process in the classroom, such as LCDs and other educational media. In addition, efforts are made to add classrooms, sports facilities, laboratories, and other amenities.